2018
DOI: 10.1037/xge0000348
|View full text |Cite|
|
Sign up to set email alerts
|

The importance of awareness for understanding language.

Abstract: Is consciousness required for high level cognitive processes, or can the unconscious mind perform tasks that are as complex and difficult as, for example, understanding a sentence? Recent work has argued that, yes, the unconscious mind can: Sklar et al. (2012) found that sentences, masked from consciousness using the technique of continuous flash suppression (CFS), broke into awareness more rapidly when their meanings were more unusual or more emotionally negative, even though processing the sentences’ meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 67 publications
4
38
2
Order By: Relevance
“…() recently proposed that multiple word expressions can be processed without conscious awareness. However, the present findings are more consistent with subsequent studies supporting the more conservative view that consciousness is required for complex cognitive tasks such as sentence comprehension and arithmetic (Moors & Hesselmann, ; Rabagliati et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…() recently proposed that multiple word expressions can be processed without conscious awareness. However, the present findings are more consistent with subsequent studies supporting the more conservative view that consciousness is required for complex cognitive tasks such as sentence comprehension and arithmetic (Moors & Hesselmann, ; Rabagliati et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Obtaining evidence for the effect in a large, independent replication study would strongly support the idea that sound-shape mapping does not require awareness. It would also suggest that suppressed word(-like) stimuli do get processed to a higher level than previously assumed (Heyman & Moors, 2014), though some researchers have posited that even semantic information can get extracted from single words under CFS (e.g., Yang & Yeh, 2011, but see Rabagliati et al, 2018, for evidence to the contrary). Failing to find a sound-symbolism congruency effect, on the other hand, would further support the idea that CFS precludes the processing of word(-like) stimuli.…”
mentioning
confidence: 97%
“…Furthermore, using the same breaking CFS paradigm, Heyman and Moors (2014) were unable to obtain standard word recognition phenomena like the effect of word frequency and lexicality. A recent paper by Rabagliati, Robertson, and Carmel (2018) featuring 10 studies found no evidence that the meaning of a phrase or a word could be processed under CFS. Taken together, there is reason to believe that CFS fundamentally disrupts the processing of word-like stimuli, yet the effect reported by Hung et al (2017) arguably depends on word recognition and interpretation processes to occur under CFS.…”
mentioning
confidence: 99%
“…Striking recent work (Hung, Styles, & Hsieh, 2017) suggests that these mappings may have an unconscious basis, such that participants can compute the fit between a word's sound and an object's shape when both are masked from awareness. This surprising finding replicated in the pre-registered report by Heyman, Maerten, Vankrunkelsven, Voorspoels and Moors (2019), with potentially far-reaching implications for the role of awareness in language processing (Hassin, 2013;Rabagliati, Robertson, & Carmel, 2018). However, as I demonstrate, it is an artifact of the stimuli used.…”
mentioning
confidence: 57%
“…Breakthrough from CFS has been used to make a number of strong claims about what can be processed without awareness, from facial emotions (Yang, Zald, & Blake, 2007) to sentence meanings (Sklar et al, 2012), but not every claim has generalized. For instance, Rabagliati et al (2018) consistently failed to replicate findings that the meanings of words NO UNCONSCIOUS SOUND SYMBOLISM 3 and phrases affected breakthrough, but did find that breakthrough was affected by low-level visual features of the stimuli (like the length of a word, or familiarity of the orthography).…”
Section: The Papers By Hung Heyman and Their Colleagues Used A Techmentioning
confidence: 93%